Soft Methods for Data Science - Ferraro, Maria Brigida; Giordani, Paolo; Vantaggi, Barbara; Gagolewski, Marek; Ángeles Gil, María; Grzegorzewski, Przemysław; Hryniewicz, Olgierd; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This proceedings volume is a collection of peer reviewed papers presented at the 8th International Conference on Soft Methods in Probability and Statistics (SMPS 2016) held in Rome (Italy). The book is dedicated to Data science which aims at developing automated methods to analyze massive amounts of data and to extract knowledge from them. It shows how Data science employs various programming techniques and methods of data wrangling, data visualization, machine learning, probability and statistics. The soft methods proposed in this volume represent a collection of tools in these fields that can also be useful for data science.
Mean Value and Variance of Fuzzy Numbers with Non-continuous Membership Functions -- On the Construction of Radially Symmetric Trivariate Copulas -- Simulation of the Night Shift Solid Waste Collection System of Phuket Municipality -- Updating Context in the Equation: An Experimental Argument with Eye Tracking -- Black-Litterman Model with Multiple Experts' Linguistic Views -- Representing Lightweight Ontologies in a Product-Based Possibility Theory Framework -- Asymptotics of Predictive Distributions -- Independent K-Sample Equality Distribution Test Based on the Fuzzy Representation -- Agglomerative Fuzzy Clustering -- Bayesian Inference with Linkage Uncertainty: Applications in Official Statistics -- The Extension of Imprecise Probabilities Based on Generalized Credal Sets -- A Generalized SMART Fuzzy Disjunction of Volatility Indicators Applied to Option Pricing in a Binomial Model -- The Representation of Conglomerative Functionals -- The Likelihood Interpretation of Fuzzy Data -- Combining the Information of Multiple Ranker in Ranked Set Sampling with Fuzzy Set Approach -- A Savage-like Representation Theorem for Preferences on Multi-acts -- On Some Functional Characterizations of (fuzzy) Set-Valued Random Elements -- Maximum Likelihood Under Incomplete Information: Toward a Comparison of Criteria -- The Use of Uncertainty to Choose Matching Variables in Statistical Matching -- Beyond Fuzzy, Possibilistic and Rough: An Investigation of Belief Functions in Clustering -- Small Area Estimation in Presence of Linkage Errors -- A Test for Truncation Invariant Dependence -- Finite Mixture Of Linear Regression Models: An Adaptive Constrained Approach to Maximum Likelihood Estimation -- Detecting Dependence in Tourists' Spending Behavior -- Robust Fuzzy Clustering via Trimming and Constraints -- One-factor Levy-frailty Copulas with Inhomogeneous Trigger Rates -- A Perceptron Classifier and Corresponding Probabilities -- Fuzzy -Signals Fed to Gaussian Channels -- Fuzzy Clustering Through Robust Factor Analyzers -- Consensus-based Clustering in Numerical Decision-Making -- Spatial Outlier Detection Using GAMs and Geographical Information Systems -- Centering and Compound Conditionals Under Coherence -- Approximate Bayesian Methods for Multivariate and Conditonal Copulae -- The Sign Test for the Interval-Valued Data -- Probability Distributions Related to Fuzzy P-Values -- Probabilistic Semantics and Pragmatics for the Language of Uncertainty -- Dynamic Analysis of the Development of Scientific Communities in the Field of Soft Computing -- Talk to your Neighbour: a Belief Propagation Approach to Data Fusion -- The Qualitative Characteristics of Combining Evidence with Discounting -- Measuring the Dissimilarity Between the Distributions of Two Random Fuzzy Numbers -- An Empirical Analysis of the Coherence Between Fuzzy Rating Scale- and Likert Scale-Based Responses to Questionnaires -- Asymptotic Results for Sums of Independent RandomVariables with Alternating Laws -- Dispersion Measures and Multidistances on Rk -- Full Conglomerability, Continuity and Marginal Extension -- On Extreme Points of P-Boxes and Belief Functions -- Modelling the Dependence in Multivariate Longitudinal Data by Pair Copula Decomposition -- Predictability in Probabilistic Discrete Event Systems -- A Sandwich Theorem for Natural Extensions -- Envelopes of Joint Probabilities with Given Marginals Under Absolute Continuity or Equivalence Constraints -- Square of Opposition Under Coherence -- Testing of Coarsening Mechanisms: Coarsening at Random Versus Subgroup Independence -- Two-sample Similarity Test for the Expected Value of Random Intervals -- Handling Uncertainty in Structural Equation Modeling -- Detecting Inconsistencies in Revision Problems -- Tukeys Biweight Loss Function for Fuzzy Set-Valued M-Estimators of Location -- Technical Gestures Recognition by Set-Valued Hidden Markov Models with Prior Knowledge -- Time Series ModelingBased on Fuzzy Transform -- Back to \Reasoning" -- Lexicographic Choice Functions Without Archimedeanicity -- Composition Operator for Credal Sets Reconsidered -- A Nonparametric Linearity Test for a Sort of Multivariate Regression Model with Fuzzy Data -- Treat a Fuzzy Dependence Among Causes and Lives in Insurance with Some Copulas Based Approaches -- A Portfolio Diversication Strategy via Tail Dependence Clustering -- An Upper Bound Estimation About the Sample Average of Interval-valued Random Sets -- On Asymptotic Properties of the Multiple Fuzzy Least Squares Estimator.
Keywords: Computational intelligence; Artificial intelligence; Probabilities; Computer science -- Mathematics; Mathematical statistics; Computational Intelligence; Artificial Intelligence; Probability Theory; Probability and Statistics in Computer Science